The Organizational Contribution of the PMO: An Assessment Using Structural Equation Modeling - El Yacoubi, Zouheir; Jahidi, Rachid (European Scientific Journal, ESJ, 2024)
This research is part of a thesis project that includes two main phases, and it aims to develop and examine a conceptual model to understand and verify the contribution of the PMO to the performance of Moroccan organizations as well as to their level of project management maturity in terms of organization and practices. Thus, the main objectives of this research are: (1) to examine the PMO’s contribution to organizational performance and project management maturity, but also (2) to contribute to consolidating the theoretical basis of the project management school. To this end, a quantitative approach was adopted, with a questionnaire administered online over three consecutive months. Firstly, the president of the Moroccan chapter of PMI was contacted to solicit his collaboration. Secondly, direct interaction was carried out with people working in project management in organizations with a Project Management Office (PMO), who were able to respond to the questionnaire via the “LinkedIn” professional network. Two hundred and five (205) responses were received, of which seventy-six (76) were discarded because respondents stated that no PMO existed within their organization, or that it had existed for less than three years. Finally, one hundred and twenty-nine (129) responses were considered usable and represented our final database from which we proceeded to a series of analyses and tests. Data analysis was carried out in two stages. First, a descriptive and exploratory analysis of the data collected was carried out using SPSS. Then, a confirmatory analysis using structural equation modeling was carried out with SmartPLS to examine the validity of the model’s concepts and test hypotheses. The results of this study provide a solid basis for linking PMO functions to organizational contributions. The study concluded that PMO functions contribute to organizational performance and project management maturity. It also highlights the mediating effect of project management maturity. However, the possible moderating effect of PMO type on structural relationships could not be verified.